Meeting of Deputy Ministers Copenhagen, Denmark. May 27, 2010. Final Participant List. - Arctic Council (2010)
Participant list from the first Deputy Ministers' Meeting of the Arctic Council held in Copenhagen, Denmark 27 May 2010.